Collaborating across cultures: Cultural metacognition and affect-based trust in creative collaboration - Chua, Roy Y.J.; Morris, Michael W.; Mor, Shira (Organizational behavior and human decision processes, 2012)
► We study how cultural metacognition influence creative collaboration in dyads. ► High cultural metacognition in dyads engenders affect-based trust and creativity. ► Affect-based trust mediates effects of cultural metacognition on creativity. We propose that managers adept at thinking about their cultural assumptions (cultural metacognition) are more likely than others to develop affect-based trust in their relationships with people from different cultures, enabling creative collaboration. Study 1, a multi-rater assessment of managerial performance, found that managers higher in metacognitive cultural intelligence (CQ) were rated as more effective in intercultural creative collaboration by managers from other cultures. Study 2, a social network survey, found that managers lower in metacognitive CQ engaged in less sharing of new ideas in their intercultural ties but not intracultural ties. Study 3 required participants to work collaboratively with a non-acquaintance from another culture and found that higher metacognitive CQ engendered greater idea sharing and creative performance, so long as they were allowed a personal conversation prior to the task. The effects of metacognitive CQ in enhancing creative collaboration were mediated by affect-based trust in Studies 2 and 3.